Computation of Gutman index of some cactus chains - Ali Sadeghieh; Nima Ghanbari; Saeid Alikhani (Electronic Journal of Graph Theory and Applications (EJGTA), 2018)
Let G be a finite connected graph of order n. The Gutman index Gut(G) of G is defined as ∑{x, y} ⊆ V(G)deg(x)deg(y)d(x, y), where deg(x) is the degree of vertex x ∈ G and d(x, y) is the distance between vertices x and y in G. A cactus graph is a connected graph in which no edge lies in more than one cycle. In this paper we compute the exact value of Gutman index of some cactus chains.